Effects of Simulation-Based Learning on Perceived Self-Efficacy of Nursing Students in Caring for Patients with Septic Shock - Srijanpal, Waraporn; Thatan, Somsri; Fukfon, Krittapat (Journal of The Royal Thai Army Nurses, 2021)
This quasi-experimental research, one group pre-posttest design, aimed to test the effect of a simulation-based learning on increasing self-efficacy among the fourth year nursing students. Participants were 113, 4th year nursing students who were studying the Nursing Care of Persons with Problem III. Research instruments composed of 1) a simulation-based learning protocol of patient with septic shock 2) high-fidelity simulation model, and 3) perceived self - efficacy questionnaire. Data were analyzed using descriptive statistic such as percentage, mean and standard deviation and paired t-test. The results showed that after the study completion, students had significant higher perceived self-efficacy score in caring for patients with septic shock than before study. Before the study a mean score of perceived self- efficacy score was 339.016 (SD = 5.67) and increased to 52.06 (SD = 4.73) after attending the simulation-based learning. This study approved that simulation-based learning method improved nursing’s student self-efficacy in caring for patients with septic shock. Also, this method can help students building their self confidence to caring patient with septic shock.